Sleeping sickness rediscovered - Welburn, S.C.; Fèvre, Eric M.; Coleman, P. (Elsevier, 1999)
This paper is a review of the meeting "Sleeping Sickness Rediscovered". The meeting focussed on human sleeping sickness, which, despite improvements in diagnosis and control has returned with a vengeance across central Africa. Topics of discussion include control activities; control tools; research; and drugs and vaccines. The paper also summarises the WHO/TDR/CTD round table which was a special session of the meeting.